R-curve behavior of silicon nitride titanium nitride composites - Choi, HJ; Cho, KS; Lee, JG; Kim, YW (AMER CERAMIC SOC, 1997)
The R-curve for Si3N4-40 wt% TiN composites was estimated by the indentation-strength method and compared to that of monolithic Si3N4 with duplex microstructure. Both materials exhibited rising R-curve behavior, The Si3N4-TiN composites, however, displayed better damage tolerance and higher resistance to crack growth. From TEM observation, it was inferred that this superior performance of Si(3)N4-TiN composites can be attributed mainly to stress-induced microcracking at heterophase (Si3N4/TiN) boundaries.
Keywords: CRACK-GROWTH-RESISTANCE; MECHANICAL-PROPERTIES; MICROCRACKING; CERAMICS; ALUMINA